The Monetarist Controversy or, Should We Forsake Stabilization Policies? - Modigliani, Franco (American Economic Review, 1977)
In recent years and especially since the onset of the current depression, the economics profession and the lay public have heard a great deal about the sharp conflict between “monetarists and Keynesians” or between “monetarists and fiscalists.” The difference between the two “schools” is generally held to center on whether the money supply or fiscal variables are the major determinants of aggregate economic activity, and hence the most appropriate tool of stabilization policies.